Investigations into the Effect of Temperature on Power-line Corona using Bridge Measuring Techniques - Pieterse, Petrus (Department of Electrical Engineering, 2024)
The need for more power and the limitations on building new power lines have made compact power lines a necessity. To design these lines, it is essential to understand the behavior of corona, which is a form of unwanted plasma discharge that causes electrical interference, power loss, and audible noise. Compact power lines require tighter conductor spacings and special high-temperature, low-sag conductors, which makes the accurate prediction of corona behavior even more crucial. This paper examines the impact of conductor temperature on corona performance, as it is an important factor that is often overlooked. Despite earlier research showing that elevated conductor temperature has a direct effect on power line corona discharge magnitude, the effect of conductor temperature on corona performance is generally not considered since the line is not expected to remain at high temperatures for extended periods and since foul weather corona is considered worse. However, since high temperature low sag conductors may operate at much higher temperatures, the effect of temperature on the corona performance has to be considered. Earlier work has shown that simple correction factors based on the assumed local reduction of air density can be applied to predict the inception value for higher conductor temperatures. Likewise, the work of Chartier and Stearns showed a dependency of the corona noise measurement on the conductor temperature, albeit only up to a temperature of 50˚C. To date no relationship between conductor temperature and corona power losses has been published. This dissertation demonstrates that losses for conductors exceeding 60˚C can be significant and follow a simple relationship with temperature. A new bridge detection method is introduced to evaluate corona loss performance by assessing positive and negative corona loss separately through postprocessing of acquired data. The experiments were performed in a laboratory using a small coaxial conductor system or corona cage with a smooth aluminium heated centre conductor ranging in temperature from 14˚C to 140˚C. The visible corona inception point is found to be lower than the point of rapid charge increase (as can be easily detected by the bridge circuit) which also follows approximately the Peek criteria with substitution of the ambient temperature for the conductor temperature, proving the bridge method to be more reliable than earlier visual observation methods. This dissertation highlights the importance of considering the effect of conductor temperature on corona performance when designing compact power lines. By doing so, the detrimental impact of corona on practical systems can be minimized.